Pemanfaatan Fly Ash pada Beton Non Pasir di Lingkungan Ekstrem - Purnamasari, Eka; Antonius, Antonius; Setiyawan, Prabowo (Universitas Veteran Bangun Nusantara, 2025)
No-Fines Concrete is a lighter type of porous concrete, which is made by removing sand from conventional concrete mixes. Fly Ash is a by-product waste from Steam Power Plants (PLTU) which use coal as fuel, in the form of fine, light, round particles and has pozzolanic properties. This research aims to evaluate the effect of using fly ash in No-Fines concrete in extreme environments, especially in peat swamp environments. The use of No-Fines concrete as a construction material is expected to reduce dependence on natural sand and utilize industrial waste such as fly ash. The peat swamp environment which has the characteristics of acidic and porous soil provides its own challenges in construction, so concrete with appropriate mechanical and physical properties is needed. The research results are expected to show that the addition of fly ash can improve the technical properties of concrete, especially in terms of strength and durability in peat swamp environments. It is hoped that it will contribute to developing environmentally friendly concrete materials and supporting the sustainability of construction in areas with extreme soil conditions. Apart from that, the use of fly ash as an additional material can help reduce industrial waste, while producing concrete that is economical and efficient to use.